GENIUS LOCI PERMUKIMAN NELAYAN PANTAI UTARA TUBAN JAWA TIMUR (Studi Kasus: Kelurahan Kingking Dan Kelurahan Karangsari) - Santri, Tyas -; Putri, Tika Novis (Jurnal Arsitektur ARCADE, 2020)
Abstract:. Tuban Regency is one of the regencies in East Java that has fishermen settlements along the north coast or on the northern coast line. The object of this study is the Kingking and Karangsari fishermen settlements located on Jalan Panglima Sudirman in Tuban Regency. The purpose of this study is to trace the genius loci which is formed from the activities of the local community where as the majority of the population earn a livelihood as a fishermen. The method used in this study is a qualitative descriptive method with a phenomenological approach. Genius loci from the location of the study is seen from the image, space, character that is formed from community activities. Data collection is done by literature study, direct observation and unstructured interviews. Image as a fishermen settlement producing smoked and fresh fish. Space there is temporel space that occurs due to new activities in places that should have certain functions for certain activities but can define other functions with other activities. The most inherent character in this study area is where the fishermen settlements that sell various types of smoked fish along the settlements are on the edge of the highway. The results of this study indicate that the existing genius loci is expected to support the development of tourism in the region.Keyword: Genius loci, fishermen settlements.Abstrak: Kabupaten Tuban merupakan salah satu kabupaten yang berada di Jawa Timur yang memiliki permukiman nelayan di sepanjang pantai utara atau di jalur pantura. Objek studi kajian ini adalah pemukiman nelayan Kingking dan Karangsari yang berada di jalan Panglima Sudirman Kabupaten Tuban. Tujuan kajian ini untuk menelusuri genius loci yang terbentuk dari aktifitas mayarakat setempat dimana sebagai mayarakat yang mayoritas bermata pencaharian nelayan. Metode yang digunakan dalam kajian ini adalah metode deskriptif kualitatif dengan pendekatan fenomenologi. Genius loci dari lokasi kajian dilihat dari image, space, character yang terbentuk dari aktifitas masyarakat. Pengumpulan data dilakukan dengan studi literatur, observasi langsung serta wawancara tidak tersetruktur. Image sebagai permukiman nelayan penghasil ikan asap dan ikan segar. Space terdapat space temporel yang terjadi akibat adanya aktifitas baru pada tempat-tempat yang seharusnya memiliki fungsi tertentu untuk aktifitas tertentu namun dapat mendefinisikan fungsi lain dengan aktifitas lain. Character yang paling melekat di kawasan studi ini adalah dimana permukiman nelayan yang menjual beragam jenis ikan asap di sepanjang permukiman ditepi jalan raya. Hasil kajian ini menunjukan genius loci yang ada diharapkan dapat menunjang pengembangan wisata kawasan tersebut.Kata Kunci: Genius loci, permukiman nelayan.